EVALUASI JALUR HIJAU TEPI JALAN KAMPUS INSTITUT PERTANIAN BOGOR DARMAGA - Dewi, Kemala; Fatimah, Indung Sitti (Jurnal Lanskap Indonesia, 2017)
This is an evaluation of roadside greenery. This evaluation was held in five main road in IPB Darmaga Campus. The aim of this activity is to identify and assess the condition of roadside greenery in IPB Darmaga. This activity was conducted as one part of the series efforts to optimize the effectiveness of roadside greenery function. The evaluation results can be used as a material consideration in the development of streetscape further. Evaluate the condition of roadside greenery by considering five aspects, such as: (1) road type and position on the road, (2) landscape regulatory and road geometry, (3) characteristics and plant growth requirements, (4) the desired function of planting and (5) psychological effects that expected from planting . They are five aspects consideration in the street scape plants application, that has been formulated by Lestari (2005). The comparative method was used to measure suitability and compatibility roadside greenery in Kampus IPB Darmaga based on landscape regulations that contained in five aspects above. Based on them, the evaluation found an information that many planting design of roadside greenery in IPB Darmaga Campus is less accordance with the planting design guidelines and principles. This was caused by disruptions due to the planting design that is too diverse in plant species selection without an appropriate arrangement with the environment. Recommended solutions to overcome this problem is by creating a more organized and themed planting design. It is more supportive for realization of the desired planting function. Recommended theme in this case is a theme that support campus visual and activity. The embodiment of such planting brings the consequence of the reduction, replacement, or addition by a more suitable plants. This activity is not an easy thing to do, it needs consideration for make it optimal and sustainable.